The relationship between school culture and school innovativeness among national type Tamil primary schools, SJK(T)S in Kuala Langat District, Selangor - Selvaraja, Kavitha; Lope Pihie, Zaidatol Akmaliah (ARC Publications, 2015)
The purpose of this was study to identify the relationship between school culture and school innovativeness in Tamil primary schools, SJK(T)s in Kuala Langat, Selangor, Malaysia. The study was also carried out to predict which school culture encourages school innovativeness. The sample consists of Tamil primary school teachers in Kuala Langat, Selangor. Nine (9) schools were selected by using cluster random sampling and all the teachers in sample schools were selected to participate in the study. A quantitative approach was used to gather data using two questionnaires which are “Organizational Culture Assessment Instrument (OCAI)” and “Public School Entrepreneurship Inventory (PSEI)”. The instruments give high cronbach alpha value which is 0.952 and 0.925 for culture and innovativeness respectively. Correlation and multiple regression analysis were used to analyze the data gathered using survey method. Result shows that Tamil primary schools, SJK(T)s in Kuala Langat, Selangor, highly practiced clan culture whereas innovativeness was practiced in moderate level. The highest correlation was observed between Market culture and innovativeness (r= .512, p<.05) whereas the lowest correlation was observed between Clan culture and innovativeness (r= .267, p<.05). Meanwhile, adhocracy and hierarchy culture have a significant correlation with innovativeness where the correlation coefficient are (r= .469, p<.05) and (r= .362, p<.05) respectively. This research indicates that market culture predicted a greater level of innovativeness than other cultures whereas hierarchy culture does not predict innovativeness in schools.